Staying Happy During COVID-19: Analyzing Happiness Indicators Among Poultry Farmers in Malang Regency - Anas Ta'in; Sutraning Nurahmi; Damat (Universitas Muhammadiyah Malang, 2024)
This study aims to examine the contribution of each happiness indicator, assess the overall happiness levels among laying hen and broiler chicken farmers, and analyze variations in happiness based on farm scale during the COVID-19 pandemic in Malang Regency. The research site was chosen through purposive sampling, as Malang Regency is a key center for poultry farming in East Java. Accidental sampling yielded 75 respondents, comprising 36 farmers with less than 5,000 livestock and 39 with more than 5,000. Results identified 16 valid indicators out of the 21 used in the study. The roles of each happiness indicator were as follows: education and skills (0.782), employment (0.780), health (0.632), family harmony (0.735), leisure availability (0.757), social relations (0.754), security conditions (0.584), happiness (0.716), absence of depression (0.793), optimism (0.867), empathy (0.570), independence (0.828), environmental mastery (0.815), self-development (0.598), positive relationships (0.615), and life goals (0.605). The overall happiness score for poultry farmers was 4.37, with laying hen farmers at 4.33 and broiler chicken farmers at 4.39, placing them in the